Interpretation of Subgrade Conditions Beneath Flexible and Rigid Pavement Layers Using Ground Penetrating Radar (GPR) - Detria Ardhila Kumala Sari; Rini Kusumawardani (Universitas Negeri Semarang, 2024)
Ground Penetrating Radar (GPR) is a device commonly utilized in non-destructive testing (NDT) applications. Its principal advantage lies in its non-invasive nature, allowing for subsurface exploration without causing damage to existing structures or the surrounding environment. Due to this characteristic, GPR has become a leading technology in subsurface investigation. GPR is regarded as an optimal solution for rapidly and efficiently assessing subsurface conditions without inflicting damage on the pavement surface. In this research, GPR technology is employed to analyze the subgrade layers beneath flexible (asphalt) and rigid (concrete) pavements, with the objective of enhancing the effectiveness and sustainability of road maintenance strategies. The data acquisition process is supported by the GAS XPC software for field data recording, while data processing is conducted using GPRSoft and GSSI RADAN 7. A comparison between raw and processed data reveals distinctions that facilitate a more in-depth analysis. Furthermore, discrepancies in data interpretation were observed between the outputs of GPRSoft and GSSI RADAN 7. These differences serve as valuable references for refining data analysis methods and improving the accuracy and reliability of future GPR-based investigations